Incidence of acquired syphilis in the municipality of Cacoal-Rondônia (Research, Society and Development, 2022)
Syphilis is a generalized and treatable infection, specific to humans, its etiologic agent is Treponema pallidum (T. pallidum). Without proper treatment, the disease progresses through the body, causing skin lesions in several parts, in the most serious forms it can lead to heart disease, nervous system compromise, total or partial blindness and even death. The objective of this study is aimed to characterize the incidence of acquired syphilis in the city of Cacoal/RO, from 2017 to 2021. As for the methodology, it is descriptive and quantitative study that used Notifiable Diseases Information System /SINAN/DATASUS as a data source. This study was approved by the Research Ethics Committee (REC), under protocol 59190722.8.0000.5298. For data analysis, the method relative and absolute frequency were used. In the years 2017 to 2021, 512 cases of acquired syphilis were reported, 301 (58.78%) correspond to male individuals, 242 (47.26%) are aged between 20 and 29 years, 111 (21.67%) have incomplete elementary education, 351 (69.33%) are brown and 480 (93.75%) live in urban areas. As for the clinical variables, all 512 cases (100%) were classified as primary syphilis, and diagnosed through clinical data and laboratory tests. In this way, it was concluded about the importance of disseminating information about the infection and its forms of contagion to society, considering that the greater the knowledge, the greater the awareness of people to protect themselves effectively, contributing to the reduction of rates. of new syphilis cases, associating these measures with professional training that reduce operational gaps for syphilis control.